2021
DOI: 10.11648/j.ajhr.20210906.14
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality Among Pregnant Women Amidst COVID-19: Association with Mental Wellbeing and Self-efficacy

Abstract: Background: Currently, corona virus disease has imposed huge global burdens and psychological impacts. Although unpredicted stress from this outbreak resulted in disturbed sleep in general, its effect on sleep among pregnant women is not well explored yet. Thus, the main aim of this study was to explore quality of sleep among pregnant mothers amidst COVID-19 pandemic. Methods: Health facility-based cross-sectional study was carried out from April to May, 2020 among 228 pregnant women. Frequencies and related p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…This is probably due to the fact that individuals, who had general anxiety symptoms, have an impact on poor quality of life and lead to poor sleep quality [59]. The finding is similar to a study done in Ethiopia [41] and the US [60].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This is probably due to the fact that individuals, who had general anxiety symptoms, have an impact on poor quality of life and lead to poor sleep quality [59]. The finding is similar to a study done in Ethiopia [41] and the US [60].…”
Section: Discussionsupporting
confidence: 78%
“…Various factors were identified as a factor of poor sleep quality in the previous studies conducted across the globe, history of abortion, comorbid depression and anxiety [39][40][41][42], gestational age (second and third trimester) [43], history of stillbirth, multigravida [44,45], individual-level of stress [44], stressful life events [41,46,47], living in rural areas [48], poor sleep hygiene [42], absence of postnatal care, current use tobacco and khat [49] were the determinant factors of poor sleep quality during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…In this systematic review and meta-analysis, we included nine cross sectional studies ( Amare, Chekol & Aemro, 2022 ; Anbesaw et al., 2021a ; Anbesaw et al., 2021b ; Bogale et al, 2022 ; Dule et al, 2021 ; Jemere et al, 2021 ; Belete et al., 2021 ; Molla, Nigussie & Girma, 2022 ; Takelle, Muluneh & Biresaw, 2022 ; Anbesaw et al., 2021b ) on the prevalence and associated factors of poor sleep quality and suicidal ideation among pregnant women during the COVID-19 pandemic in Ethiopia. Based on the types of mental disorders; six studies ( Amare, Chekol & Aemro, 2022 ; Bogale et al, 2022 ; Anbesaw et al., 2021a ; Anbesaw et al., 2021b ; Jemere et al, 2021 ; Takelle, Muluneh & Biresaw, 2022 ; Dule et al, 2021 ) were reported about poor sleep quality; three studies ( Belete et al., 2021 ; Anbesaw et al., 2021b ; Molla, Nigussie & Girma, 2022 ) were reported about suicidal ideation. Furthermore, the summarized data of the key characteristics of the included studies for this review were showed in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Women who are on antenatal care developed suicidal ideation due to different factors including, absence of cohabiting partners, history of abortion, depression, anxiety, intimate partner violence, poor sleep quality and stress ( Anbesaw et al., 2021b ). There are single level study findings in Ethiopia ( Amare, Chekol & Aemro, 2022 ; Anbesaw et al., 2021a ; Bogale et al, 2022 ; Dule et al, 2021 ; Jemere et al, 2021 ; Belete et al., 2021 ; Molla, Nigussie & Girma, 2022 ; Takelle, Muluneh & Biresaw, 2022 ; Anbesaw et al., 2021a ) on the prevalence of poor sleep quality and suicidal ideation among pregnant women during COVID-19. The reports on prevalence of poor sleep quality and suicidal ideation in Ethiopia were high, and the results were inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…These enacted measures from the governments of the respective countries had a detrimental effect on the social and psychological well-being of citizens, especially students [ 14 ]. It was apparent from the restrictions on students that their physical activity (PA) behavior and well-being would be adversely affected [ 15 ], because the students were exposed to psychological fatigue and limited physical activities due to the restrictions following the cessation of all sports and educational activities, such as stadiums and recreation facilities [ 16 , 17 ]. The aftermath effect of these setbacks created an imbalance in the mental well-being, PA, motivated behavior status, and concentration amongst students [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%